A simple amide fluorescent sensor based on quinoline for selective and sensitive recognition of zinc(II) ions and bioimaging in living cells. (November 2018) - Liu, Haiyang; Tan, Ying; Dai, Qiuzi; Liang, Hongda; Song, Jun; Qu, Junle; Wong, Wai-Yeung
Abstract: A simple quinoline-based derivative (AQDPA) was developed as a highly efficient fluorescent sensor for sensing Zn 2+ and sequential recognition of pyrophosphate and sulfur ions. This chemosensor was synthesized from diisopropylamine and 2-chloro-N-(quinolin-8-yl)acetamide. The non-fluorescence sensor displayed significant and specific fluorescence enhancement after binding to Zn 2+ with high selectivity. The fluorescence titration analysis shows a detection limit for Zn 2+ at 4.1 × 10 −8 M. The sensing mechanisms of AQDPA binding to Zn 2+ were supported by 1 H NMR, HR-MS analysis, and density functional theory (DFT) study. Moreover, the fluorescence imaging in HeLa cells suggested that this simple sensor had great potential in the application of biological imaging. Graphical abstract: A simple quinoline-based derivative (AQDPA) was developed as a highly efficient fluorescent sensor for detecting Zn 2+ with obvious fluorescence enhancement over other common metal ions, and the resulting complex AQDPA-Zn 2+ was also determined to act as a cascade sensor for recognizing pyrophosphate (PPi) and S 2− . Image 1 Highlights: An efficient quinoline-based fluorescent sensor for Zn 2+ detection is reported. A binding mode is proposed via NMR, HRMS analysis, and DFT studies. The chemosensor with low cytotoxicity is used for imaging of Zn 2+ in living cells.